EXPERIMENTAL INVESTIGATION OF A PARAFFIN BASED HYBRID ROCKET - Santos, L. M. C.; Almeida, L. A. R.; Fraga, A. M.; Veras, C. A. G. (Revista de Engenharia Térmica, 2006)
Hybrid rockets are known to be simpler, safer, environmentally friend, and, more importantly, cheaper than most of the technologies for propulsion devices used today. Hybrid rockets can be applied as the propulsion system in satellites launch vehicles, micro-satellites and tactical missiles. This paper deals with combustion of ultra-high molecular weight polyethylene (UHMWPE) and paraffin as the solid fuels burning with gaseous oxygen (GOX) as well as N O as the oxidizer in lab scale hybrid rocket motors. A test 2 stand was built to carry out the experiments. The main objectives were to investigate the ignition of the solid fuels, burning performance and regression rates for different operating conditions. With paraffin-based fuel the hybrid motor had the regression rate enhanced two to three folds compared to the UHMWPE, as reported in the literature. The overall performance of the motor, with paraffin as the fuel, is comparable to other technologies. Paraffin-based hybrid rockets can, then, be a safer and cheaper alternative to satellite launch vehicles for the Brazilian space program.